Temperature dependence of ferromagnetic resonance in double perovskite La2NiMnO6 thin films - Kazan, Sinan (Sakarya University, 2021)
The results of the linewidth analysis of ferromagnetic resonance (FMR) spectra of epitaxial La2NiMnO6 (LNMO) thin films on (100) oriented SrTiO3 and (110) oriented NdGaO3 substrates at different temperature have been presented. Observed two well resolved FMR signals have been attributed to the coexistence two magnetic phases with different easy and hard axis in the film plane of LNMO. The line shape and the linewidth of the ferromagnetic resonance spectra were measured as a function of temperature. Asymmetry ratio of field derivative FMR absorption curve shows unusual behavior with decreasing temperature. This unusual temperature dependency of the FMR linewidth confirms the presence of magnetoelectric effect in epitaxial LNMO thin films grown by pulse laser deposition technique. © 2025 Elsevier B.V., All rights reserved.
Keywords: Double perovskite; Ferromagnetic Resonance; La2NiMnO6; Magnetodielectric